Exploring Muslim Women Pioneers Who Contributed to the Glory of Islamic Civilization from the Advent of Islam to the End of the 13th Century AH (19th Century CE) - Mohammed Houmine (UIN Sunan Gunung Djati Bandung, 2024)
The West's view of Muslim women is not devoid of attitudes that relegate them to a kind of inferiority, as enslaved and humiliated, whose main task is to reproduce, educate, cook, wash and so on. In fact, the word